2014
DOI: 10.1186/1471-230x-14-4
|View full text |Cite
|
Sign up to set email alerts
|

A non-interventional study of the genetic polymorphisms of NOD2 associated with increased mortality in non-alcoholic liver transplant patients

Abstract: BackgroundInfections after liver transplantation are the main cause of death in the first year. Recent reports indicate that NOD2 gene mutations increase the risk for inflammatory bowl disease and the severity of graft-versus-host disease in bone marrow transplant patients. Data on polymorphisms in liver transplant patients are sparse. We analyzed 13 single-nucleotide polymorphisms (SNPs) of 13 different gene variants including the SNPs of NOD2 genes from liver recipients. The aim of the study was to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…We recorded a 27.9% acute rejection rate associated with the CT genotype compared with 12.5% in relation to the TT genotype at rs2066844. These results are in agreement with those obtained from other studies, including our own, where polymorphisms in this gene influence the organ survival outcomes of transplant patients [ 20 , 47 , 48 ]. Due to the potential relevance of this finding, we think that this gene should be included in future studies including more patients.…”
Section: Resultssupporting
confidence: 93%
“…We recorded a 27.9% acute rejection rate associated with the CT genotype compared with 12.5% in relation to the TT genotype at rs2066844. These results are in agreement with those obtained from other studies, including our own, where polymorphisms in this gene influence the organ survival outcomes of transplant patients [ 20 , 47 , 48 ]. Due to the potential relevance of this finding, we think that this gene should be included in future studies including more patients.…”
Section: Resultssupporting
confidence: 93%
“…Genetic polymorphisms of NOD2 are associated with increased mortality in nonalcoholic liver transplant patients 44 . Inflammasomes recognize pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs) that cleavage proinflammatory cytokines such as pro-interleukin (IL)-1β 44 and pro-IL-18.…”
Section: Factors Contributing To Intestinal Dysbiosismentioning
confidence: 99%
“… 42 , 43 Genetic polymorphisms of NOD2 are associated with increased mortality in nonalcoholic liver transplant patients. 44 Inflammasomes recognize pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs) that cleavage proinflammatory cytokines such as pro-interleukin (IL)-1β 44 and pro-IL-18. Mice deficient for nucleotide-binding domain and leucine-rich repeat-containing protein 6 (NLRP-6), and hence less intestinal IL-18, showed altered fecal microbiota characterized by an increase of the bacterial phyla Bacteroidetes (Prevotellaceae) and TM7.…”
Section: Factors Contributing To Intestinal Dysbiosismentioning
confidence: 99%
“…In addition, essentially all animal models of intestinal fibrosis appear to be dependent on the presence of a microflora to initiate or perpetuate gut inflammation and fibrosis [25]. Although direct evidence about the innate immunity gene variants in liver fibrosis is lacking, several studies have shown that NOD2 is associated with the increased mortality in nonalcoholic liver transplant patients [30] or the increased risk of spontaneous bacterial peritonitis in patients with liver cirrhosis [31,32]. …”
Section: Innate Immunitymentioning
confidence: 99%